2013
DOI: 10.1116/1.4775789
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the composition of lead zirconate titanate by atomic layer deposition

Abstract: The incubation time during atomic layer deposition (ALD) of lead oxide, zirconium oxide, and titanium oxide on each other was quantified in order to precisely control the composition of lead zirconate titanate (PZT). The desired stoichiometry of Pb:Zr:Ti¼2:1:1, which yields the desired ferroelectricity, was found to depend strongly on the ALD sequence, the substrate of choice, as well as the postdeposition annealing temperature. With the desired stoichiometry, the ferroelectric and piezoelectric properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In 2013, Choi et al also published results showing how the composition in the PbTiO 3 ‐PbZrO 3 ‐system was highly tunable in ALD . By using Pb(thd) 2 , Ti(O i Pr) 2 (thd) 2 and Zr(thd) 4 , Choi's group was able to precisely tune the composition around the morphotropic phase boundary, showing that it is indeed feasible to use ALD for obtaining very thin and conformal layers of complex materials.…”
Section: The Current Toolboxmentioning
confidence: 99%
“…In 2013, Choi et al also published results showing how the composition in the PbTiO 3 ‐PbZrO 3 ‐system was highly tunable in ALD . By using Pb(thd) 2 , Ti(O i Pr) 2 (thd) 2 and Zr(thd) 4 , Choi's group was able to precisely tune the composition around the morphotropic phase boundary, showing that it is indeed feasible to use ALD for obtaining very thin and conformal layers of complex materials.…”
Section: The Current Toolboxmentioning
confidence: 99%
“…Also, there is typically a non‐linear relationship between growth per cycle (GPC), composition and cation cycle ratio 24 . Pb‐loss during the crystallization anneal has also been shown to affect film stoichiometry 25 . Despite these challenges, Hwang et al previously grew ALD PTO with promising ferroelectric properties (following post‐deposition anneal) for FRAM using lead bis(3‐N,N‐dimethyl‐2‐methyl‐2‐propanoxide) [Pb(DMAMP) 2 ] as the lead precursor, with the leakage current reported to be higher than 1 A/cm 2 at ±1 V and dissipation factor higher than 0.2 at ±2 V 26 .…”
Section: Introductionmentioning
confidence: 99%
“…24 Pb-loss during the crystallization anneal has also been shown to affect film stoichiometry. 25 Despite these challenges, Hwang et al previously grew ALD PTO with promising ferroelectric properties (following post-deposition anneal) for FRAM using lead bis(3-N,N-dimethyl-2-methyl-2-propanoxide) [Pb(DMAMP) 2 ] as the lead precursor, with the leakage current reported to be higher than 1 A/cm 2 at ±1 V and dissipation factor higher than 0.2 at ±2 V. 26 Watanabe et al previously reported ALD PZT using β-diketonate precursors for the Pb and Zr cations and titanium tetraisopropoxide (TTIP) for the Ti cation, though the leakage current density wasn't directly reported and the TTIP dose did not saturate. 24 Thus, there is the need for continued process development of ALD PZT toward improved electronic properties, lower leakage current density, and optimized precursor dose saturation.…”
mentioning
confidence: 99%
“…Due to the fact that the PZT was interfaced with MgO on both sides, the interfacial dead layer that is intrinsic to the electrode/dielectric boundary is expected to be negligible in our film. 39 PZT deposition was performed via ALD, 40,41 which has been previously shown to provide conformal atomically smooth ultra-thin films with precise control over composition and thickness. 42 MTJs with a pure MgO tunnel barrier were used as the reference sample and compared to the MTJs with the MgO/ PZT/MgO tunnel barrier (hereafter referred to as MgO MTJ and PZT MTJ, respectively).…”
mentioning
confidence: 99%
“…The synthesis of PZT thin film has been outlined in previous papers. 40,41 The PZT MTJ film stack was annealed at 200 C under vacuum both before the PZT deposition and after depositing the whole film stack. Since the PZT MTJ film stack was also in-situ annealed during the ALD process under 250 C, the MgO MTJs were annealed at 250 C for a fair comparison.…”
mentioning
confidence: 99%